2021
DOI: 10.1111/jopr.13428
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Titanium and Fiber Dental Posts: A Systematic Review and Meta‐Analysis

Abstract: Purpose The fracture resistance of dental post systems is influenced by the material of the post. The purpose of this systematic review and meta‐analysis was to assess if there is a difference in fracture resistance between prefabricated dental titanium posts and fiber posts. Methods An online electronic search was performed using the PubMed, Scopus, and Web of Science databases for in vitro studies published from 2010 to 2020 in English. The retrieved eligible studies that compared the fracture resistance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…An assessment of the risk of bias was undertaken as described by Uzunoglu-Özyürek et al and Alhajj et al 15,16 In each included study, the following parameters were evaluated: randomization of teeth, the presence of control, standardization of teeth dimensions, reporting of age, description of sample size calculation, the use of materials according to the manufacturer's instructions, samples prepared by a single operator, and blinding of the observer during fracture test. The presence of each parameter was recorded as "yes," whereas absence was recorded as "no."…”
Section: Methodsmentioning
confidence: 99%
“…An assessment of the risk of bias was undertaken as described by Uzunoglu-Özyürek et al and Alhajj et al 15,16 In each included study, the following parameters were evaluated: randomization of teeth, the presence of control, standardization of teeth dimensions, reporting of age, description of sample size calculation, the use of materials according to the manufacturer's instructions, samples prepared by a single operator, and blinding of the observer during fracture test. The presence of each parameter was recorded as "yes," whereas absence was recorded as "no."…”
Section: Methodsmentioning
confidence: 99%
“…9,41 In comparison with fiber posts, a systematic review concluded that titanium and fiber posts show similar fracture resistance. 10 Glass fiber resin post systems that are formed from unidirectional glass fibers embedded in a resin matrix are reported to lower the risk of fractures of restored roots. 42 Elasticity of dentin is 20 Gpa, and glass fiber posts with a 40 Gpa modulus of elasticity would be an ideal post material.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the mode of fracture, based on the articles included in this study and a systematic review, in comparison to metal posts, fiber posts have considerably demonstrated less severe root fractures. 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations